KETERSANDUNGAN ALIRAN KEPERCAYAAN DALAM POLITIK IDENTITAS SISTEM PENDIDIKAN NASIONAL - Indra Jaya K Wardhana (Universitas Trunojoyo Madura, 2023)
The religious beliefs adherents are experiencing a contradictions in national education system. Where regulation and educational policies at the Ministry of National Education level and at the level of educational institutions, do not accommodate the interest of students who adhere of religious beliefs as a cultural heritage. Through the implementation of education, students who adhere of religious beliefs, experience a discrimination in the implementation of education through standardization of education. At the same time, the existence as an embodiment of politics identity is exist in responding the issue of equality. This reconciliation, deconstructs the policy which is regulated in the circular letter